Profit And Loss Analysis Of Porang (Amorphophallus Oncophyllus Prain) Farming In Tegalwaru District Karawang Regen - Santi Lestari; Sulistyo Sidik Purnomo; I Putu Eka Wijaya (UNIVED Press, Dehasen University Bengkulu, 2023)
Porang is a tuber plant that has the potential to develop because it has export market opportunities as industrial raw material. Tegalwaru District, Karawang Regency is one of the areas that produces porang, to cultivate porang requires a large enough capital to become one of the obstacles to porang farming. This study aims 1) to determine the amount of acceptance and income of porang farmers in Tegalwaru District, Karawang Regency and; 2) to obtain information on the profit and loss of porang farming in Tegalwaru District, Karawang Regency. The research method used is a case study. This research was conducted from June to July in Tegalwaru District, Karawang Regency. Sampling technique using saturated sampling method. Data collection uses primary data and secondary data. The analysis used is revenue, revenue, R/C, revenue BEP, production BEP and price BEP and payback period. The results showed an average total cost of IDR 67,126,783 per planting season, an average revenue of IDR 156,482,759. per planting season and an average income of Rp 89.818.919. R/C Ratio value of 2.33. The BEP value of revenue is Rp. 2,407,468, - the production BEP is 601,87 kg and the price BEP is IDR 1,715/kg. The payback period for porang farming is 7 months